[Disability and work: summary of policy evolution, from the UN Convention to European Union Strategies] - Persechino, Benedetta; Fortuna, Grazia; Dentici, Maria Cristina; Valenti, Antonio; Iavicoli, Sergio (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Over the last decades the concept of disability has undergone a radical evolution: from a "status" recipient of passive and welfare policies it evolved to a "social relationship" model based on individual factors and environmental conditions. As a consequence, the strategies of supranational and international organizations have also evolved, embracing the changes that have occurred in the cultural and scientific paradigms relating to this issue. This study aims to explain a summary of the regulations and documents produced, in particular in the European Union (EU), to support the protection and social participation of disabled people, based on the three fundamental elements: the guarantee of individual rights to eliminate discrimination, the elimination of environmental barriers, the promotion of an active inclusion of people with disabilities. Specifically, the EU has developed over time valid strategies based on the cultural and regulatory framework validated by the UN Convention on the rights of people with disabilities. The recent European Strategy for the Rights of Persons with Disabilities 2021-2030 represents an opportunity to contribute to a real inclusion of people with disabilities in all contexts, including the workplace, in order to guarantee good health and safety conditions.